2012
DOI: 10.1126/science.1221329
|View full text |Cite
|
Sign up to set email alerts
|

Seemingly Anomalous Angular Distributions in H + D 2 Reactive Scattering

Abstract: When a hydrogen (H) atom approaches a deuterium (D(2)) molecule, the minimum-energy path is for the three nuclei to line up. Consequently, nearly collinear collisions cause HD reaction products to be backscattered with low rotational excitation, whereas more glancing collisions yield sideways-scattered HD products with higher rotational excitation. Here we report that measured cross sections for the H + D(2) → HD(v' = 4, j') + D reaction at a collision energy of 1.97 electron volts contradict this behavior. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 20 publications
5
48
0
Order By: Relevance
“…Actual recoil values are tabulated in Table 1. In our earlier studies this inherent uncertainty in the speed of HD(ν , j ) product was taken into account by convoluting the theoretical calculations with a ∼ 200 m/s wide Gaussian, i.e., typical HD + recoil values, see Table 1 [7][8][9]. Here we add the appropriate error bars on experimentally measured points rather than further blurring theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Actual recoil values are tabulated in Table 1. In our earlier studies this inherent uncertainty in the speed of HD(ν , j ) product was taken into account by convoluting the theoretical calculations with a ∼ 200 m/s wide Gaussian, i.e., typical HD + recoil values, see Table 1 [7][8][9]. Here we add the appropriate error bars on experimentally measured points rather than further blurring theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, similar conclusions were reached by Fernandez-Alonso et al [40] who measured the D 2 (v = 0, j) reactant rotational state distribution and found that about 10% of the population resides in D 2 (v = 0, j > 2) states. Subsequently, all theoretical calculations on H + D 2 reaction were performed assuming only three initial reactant states, i.e., D 2 (v = 0, j ≤ 2), and the agreement in most cases was found to be very good [7][8][9]. The last source of uncertainty in the experimental measurement of HD(ν , j ) laboratory speed is the HD + recoil imparted by the departing electron.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations